1999
DOI: 10.1046/j.1365-2672.1999.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of temperature and nutrients on the survival ofCampylobacterspp. in water microcosms

Abstract: C . T HO M AS , D . J. HI L L A ND M .M AB E Y. 1999. Batch microcosms containing various water types (de-ionized and river water with or without sediment), incubated at a range of temperatures (5-37°C), were used to facilitate a comparative evaluation of the significance of such variables and their interactions upon the collective and individual survival of four species of thermophilic Campylobacter. All variables significantly influenced (P ³ 0·031) population decay rates. Minimal decay for the group was ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
96
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(111 citation statements)
references
References 26 publications
12
96
3
Order By: Relevance
“…It has also been reported that a laboratory strain of C. coli is less well adapted to survival in water than C. jejuni or C. lari is (37). The present study supports the view that C. coli is widely distributed in environmental water and further suggests the possibility that there is a strain or strains associated with this medium, whose existence would have significant ramifications for exposure risks associated with environmental water sources.…”
Section: Vol 70 2004 Characteristics Of C Coli From Cheshire Studysupporting
confidence: 77%
“…It has also been reported that a laboratory strain of C. coli is less well adapted to survival in water than C. jejuni or C. lari is (37). The present study supports the view that C. coli is widely distributed in environmental water and further suggests the possibility that there is a strain or strains associated with this medium, whose existence would have significant ramifications for exposure risks associated with environmental water sources.…”
Section: Vol 70 2004 Characteristics Of C Coli From Cheshire Studysupporting
confidence: 77%
“…In surface waters, sunlight reduces the longevity of bacteria, whereas factors, such as turbidity that decrease the transmission of light tend to increase survival time (Aramini et al, 2000). Campylobacter survival rates in freshwater can be up to 4 months with survival greatest at 4 1C (Rollins and Colwell, 1986;Thomas et al, 1999). Survival time, however, is highly dependent upon strain type, previous growth conditions, water quality, and environmental conditions (Buswell et al, 1998(Buswell et al, , 1999.…”
Section: Persistence Of Pathogens In the Environmentmentioning
confidence: 99%
“…Experimental evidence suggests that under such conditions C. jejuni generates forms that are viable but nonculturable, especially in the presence of biofilms derived from poultry houses (101). The survival of such forms for periods of up to 4 months has been recorded (79), but survival times appear to vary with water temperature, strain, the aquatic system used, and previous growth conditions (11,98,99). There has been considerable debate as to whether such water-stressed bacteria retain infectivity.…”
Section: Sources Of Poultry Colonizationmentioning
confidence: 99%